2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5627303
|View full text |Cite
|
Sign up to set email alerts
|

PSS-SQL: Protein Secondary Structure - Structured Query Language

Abstract: Secondary structure representation of proteins provides important information regarding protein general construction and shape. This representation is often used in protein similarity searching. Since existing commercial database management systems do not offer integrated exploration methods for biological data e.g. at the level of the SQL language, the structural similarity searching is usually performed by external tools. In the paper, we present our newly developed PSS-SQL language, which allows searching a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…the primary, secondary and tertiary level. In [33] and [34], we reported the PSS-SQL (Protein Secondary Structure -Structured Query Language) for searching protein similarities on the basis of their secondary structures in the Microsoft SQL Server relational database. The newest version of the PSS-SQL search engine [35] utilizes a multi-threaded alignment procedure, which allows effective querying on DBMSs hosted on computers with multi-core CPUs.…”
Section: B Related Workmentioning
confidence: 99%
“…the primary, secondary and tertiary level. In [33] and [34], we reported the PSS-SQL (Protein Secondary Structure -Structured Query Language) for searching protein similarities on the basis of their secondary structures in the Microsoft SQL Server relational database. The newest version of the PSS-SQL search engine [35] utilizes a multi-threaded alignment procedure, which allows effective querying on DBMSs hosted on computers with multi-core CPUs.…”
Section: B Related Workmentioning
confidence: 99%
“…The BioSQL [25], which incorporates modules of the BioJava project [26], focuses on biomolecular sequences and features, their annotation, a reference taxonomy, and ontologies. Several extensions to the SQL language, including PSS-SQL [27,28] and the query language developed by Hammel and Patel [29] and Tata et al [30], were proposed for searching protein similarities on the basis of protein secondary structures. These works show how protein data can be stored in relational tables.…”
Section: Related Workmentioning
confidence: 99%
“…Protein-QL allows to formulate simple queries that operate on the primary, secondary and tertiary level. Finally, in Małysiak- Mrozek et al (2012) and Mrozek et al (2010), we reported the PSS-SQL (Protein Secondary Structure -Structured Query Language) that allows to search for protein similarities on the basis of secondary structures. The search engine of the PSS-SQL utilized a single-thread alignment procedure, which we found insufficient for effective processing in the era of multi-core CPUs.…”
Section: Related Workmentioning
confidence: 99%